8/10 two‐dimensional modulation code for holographic data storage systems. Issue 9 (12th April 2016) - Nguyen, C.D.; Lee, J.
Abstract : Holographic data storage (HDS) provides the high storage density and fast data‐access rate because of the page‐oriented data processing, and by the same reason, the performance of retrieving original user data is mainly affected by 2D intersymbol interference (ISI). An 8/10 2D modulation code for mitigating a 2D ISI in HDS systems is proposed. The simulation results show that the proposed code provides a gain of approximately 6 dB at BER of 10 −6 compared to the raw signal without encoding. Especially, in comparison to a recently suggested 6/8 modulation code, the proposed scheme not only offers a higher code rate, but it also exposes a boost of the system performance under misalignment conditions.